POOR REDUCTION AND ENTREPRENEURSHIP DEVELOPMENT IN UZBEKISTAN - Isakov Musoxon Yusupdjanovich (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
The article explores some of the key areas for further poverty reduction and entrepreneurship development by further improving the business environment in the current context of the ongoing pandemic.